2021
DOI: 10.1155/2021/6463281
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Degraded Porphyra yezoensis Polysaccharides on the Oxidative Damage of Renal Epithelial Cells and on the Adhesion and Endocytosis of Nanocalcium Oxalate Crystals

Abstract: The protective effects of Porphyra yezoensis polysaccharides (PYPs) with molecular weights of 576.2 (PYP1), 105.4 (PYP2), 22.47 (PYP3), and 3.89 kDa (PYP4) on the oxidative damage of human kidney proximal tubular epithelial (HK-2) cells and the differences in adherence and endocytosis of HK-2 cells to calcium oxalate monohydrate crystals before and after protection were investigated. Results showed that PYPs can effectively reduce the oxidative damage of oxalic acid to HK-2 cells. Under the preprotection of PY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Thus, the results indicated that molecular weight affected the oxidative stress activity of sea cucumber polysaccharides. Peng et al [ 38 ] obtained the degradation products of Porphyra yezoensis polysaccharides with different molecular weights through H 2 O 2 degradation and observed the same trend when studying its oxidative stress activation on human renal epithelial cells. Fang et al [ 39 ] found that the enzymatic degradation product of the Gracilariopsis lemaneiformis polysaccharide had a better effect in alleviating oxidative damage in HFL1 cells compared to the original polysaccharide.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the results indicated that molecular weight affected the oxidative stress activity of sea cucumber polysaccharides. Peng et al [ 38 ] obtained the degradation products of Porphyra yezoensis polysaccharides with different molecular weights through H 2 O 2 degradation and observed the same trend when studying its oxidative stress activation on human renal epithelial cells. Fang et al [ 39 ] found that the enzymatic degradation product of the Gracilariopsis lemaneiformis polysaccharide had a better effect in alleviating oxidative damage in HFL1 cells compared to the original polysaccharide.…”
Section: Discussionmentioning
confidence: 80%
“…Diminishing crystal adhesion on cell surfaces is an imperative strategy to thwart stone formation [ 64 ]. A prior study from our laboratory [ 65 ] revealed that damaged HK-2 cells, upon repair by polysaccharides, showcased marked reductions in OPN expression.…”
Section: Discussionmentioning
confidence: 99%
“…93 The process of CaP precipitation in basement membranes involved the following mechanism: The basement membranes of the thin Henle loops are relatively thick and primarily composed of collagens, which along with a substantial presence of mucopolysaccharides, and provide numerous electrostatically binding sites for calcium and phosphate ions. 81 As there was evidence that CaP supersaturation, occurring in the thin Henle loops, adequately induced CaP crystallization, 94 and a few studies have reported the endocytosis of crystals by tubular epithelial cells, [95][96][97] thus there exist arguments that CaP crystals, originating in the tubular lumen, may be endocytosed and exocytosed by cells and then deposit in basement membranes. 77,91,94 Additionally, impaired functions of the tight junction, impairing paracellular permeability and barrier function, may be involved in the translocation of crystals.…”
Section: The Forming Pro Ce Ss E S Of C Alcified Pl Aque S In Renal I...mentioning
confidence: 99%
“…As there was evidence that CaP supersaturation, occurring in the thin Henle loops, adequately induced CaP crystallization, 94 and a few studies have reported the endocytosis of crystals by tubular epithelial cells, 95 , 96 , 97 thus there exist arguments that CaP crystals, originating in the tubular lumen, may be endocytosed and exocytosed by cells and then deposit in basement membranes. 77 , 91 , 94 Additionally, impaired functions of the tight junction, impairing paracellular permeability and barrier function, may be involved in the translocation of crystals.…”
Section: The Forming Processes Of Calcified Plaques In Renal Intersti...mentioning
confidence: 99%